Self-Assessment of Hearing and Purchase of Hearing Aids by Middle-Aged and Elderly Adults - Otavio, Andressa Colares da Costa; Coradini, Patricia Pérez; Teixeira, Adriane Ribeiro (International Archives of Otorhinolaryngology, 2016)
Introduction Presbycusis is a consequence of aging. Prescription of hearing aids is part of the treatment, although the prevalence of use by elderly people is still small.Objective To verify whether or not self-assessment of hearing is a predictor for purchase of hearing aids.Methods Quantitative, cross-sectional, descriptive, and observational study. Participants were subjects who sought a private hearing center for selection of hearing aids. During the diagnostic interview, subjects answered the following question: “On a scale of 1 to 10, with 1 being the worst and 10 the best, how would you rate your overall hearing ability?” After that, subjects underwent audiometry, selected a hearing aid, performed a home trial, and decided whether or not to purchase the hearing aid. The variables were associated and analyzed statistically.Results The sample was comprised of 32 subjects, both men and women, with a higher number of women. Mean age was 71.41 ± 12.14 years. Self-assessment of hearing ranged from 2 to 9 points. Overall, 71.9% of the subjects purchased hearing aids. There was no association between scores in the self-assessment and the purchase of hearing aids (p = 0.263). Among those who scored between 2 and 5 points, 64.7% purchased the device; between 6 and 7 points, 76.09% purchased the device; and between 8 and 9 points, 50% purchased the device, respectively.Conclusion There is evidence that low self-assessment scores lead to the purchase of hearing aids, although no significant association was observed in the sample.
Keywords: self-assessment; hearing aids; elderly